2y^2-3y-6=0

1 Answer | Add Yours

llltkl's profile pic

llltkl | College Teacher | (Level 3) Valedictorian

Posted on

`2y^2-3y-6=0`  is a quadratic equation in the form of `ay^2+by+c=0` where `a=2` ,`b=-3` and `c=-6.`

Therefore, using the quadratic formula to solve for 'y' we get:

`y=(-b+-sqrt(b^2-4ac))/(2a)`

`=(-(-3)+-sqrt((-3)^2-4*2*-6))/(2*2)`

`=(3+-sqrt(9+48))/4`

`=(3+-sqrt(57))/4`

So, the solutions are  `y=(3+sqrt(57))/4` and `y=(3-sqrt(57))/4` .





 




 


Sources:

We’ve answered 318,913 questions. We can answer yours, too.

Ask a question